Dynamic structure evolution and failure mechanism of nanocrystalline AlCo-CrFeNi - ZHANG Rong; QI Wenjun (Cailiao gongcheng)
The molecular dynamics method was used to simulate the microstructure dynamic evolution， dislocation， and pore motion characteristics of AlCoCrFeNi high-entropy alloy at temperature 300 K and strain rate of 1×109 s-1， and the failure mechanism was revealed. The simulation results show that the maximum load-bearing， longitudinal modulus， and ductility of the nano-polycrystalline AlCoCrFeNi high-entropy alloy are lower than those of nano-monocrystalline. The strain reduction and peak stress reduction of nano-polycrystalline before yield are 25% and the peak stress reduction is 23.8%. The phase transition， dislocation， hole， and failure mechanism of the two nanocrystallines are different during the stretching process. During the stretching process of nano-monocrystals， the FCC structure is mainly transformed into a non-crystalline structure. The atomic position changes after the phase change， accompanied by a large number of Shorkly dislocations， and moves with the growth direction of the non-crystalline structure. The hole nucleation， growth， penetration， and failure fracture of non-crystalline structure area are mainly amorphous perforation fault. During the stretching process of nano-polycrystalline， the FCC structure mainly transforms to HCP structure and non-crystalline structure， and the atomic position changes after the phase change， accompanied by a large number of 1/6〈112〉 （Shortly） dislocations and a small number of 1/6〈110〉 （Stair-rod） dislocations， 1/3〈100〉 （Hirth） dislocations， and other dislocations continue to be generated and annihilated.The material undergoes certain plastic deformation， with nucleation of pores in the non-crystalline structure area of the grain boundary， growth and expansion along the grain boundary， and penetration through the grain boundary until failure fracture， showing mainly intergranular fracture.